A Communication Training Program to Encourage Speaking‐Up Behavior in Surgical Oncology. (27th September 2017) - D'Agostino, Thomas A.; Bialer, Philip A.; Walters, Chasity B.; Killen, Aileen R.; Sigurdsson, Hrafn O.; Parker, Patricia A.
Abstract: Patient safety in the OR depends on effective communication. We developed and tested a communication training program for surgical oncology staff members to increase communication about patient safety concerns. In phase one, 34 staff members participated in focus groups to identify and rank factors that affect speaking‐up behavior. We compiled ranked items into thematic categories that included role relations and hierarchy, staff rapport, perceived competence, perceived efficacy of speaking up, staff personality, fear of retaliation, institutional regulations, and time pressure. We then developed a communication training program that 42 participants completed during phase two. Participants offered favorable ratings of the usefulness and perceived effect of the training. Participants reported significant improvement in communicating patient safety concerns ( t 40 = –2.76, P = .009, d = 0.48). Findings offer insight into communication challenges experienced by surgical oncology staff members and suggest that our training demonstrates the potential to improve team communication.